The Implementation of the Convention on the Rights of Persons with Disabilities: More Than Just Another Reform of Psychiatry - Jasna Russo; Stephanie Wooley (Harvard FXB Center for Health and Human Rights, 2020)
The social model of disability-which is grounded in the lived realities of disabled people, as well as their activism, research, and theoretical work-has enabled a historic turn in the understanding of disability. This model also facilitates the transition to the rights-based approach that is at the core of the United Nations Convention on the Rights of Persons with Disabilities (CRPD). However, the social model of disability does not straightforwardly translate to the lives of people who end up being detained and forcibly treated in psychiatric facilities. This paper examines the implications of the lack of an equivalent theoretical framework to counteract the hegemony of the biomedical model of "mental illness" and to underpin and guide the implementation of the CRPD for people with psychiatric diagnoses. Critically engaging with some recent attempts to make the CRPD provisions integral to psychiatry, we expose fundamental contradictions inherent in such projects. Our discussion seeks to extend the task of implementation of the CRPD beyond reforming psychiatry, suggesting a much broader agenda for change. We argue for the indispensability of first-person knowledge in developing and owning this agenda and point to the dangers of merely remaking former treatment objects into objects of human rights.